Performance with different loss functions. “ ” and “**” denote significance levels of and , respectively, from a two-sided paired t-test when comparing our best model with others. The best results are shown in bold. - Hua Wang (13530) (2025)
Performance with different loss functions. “ ” and “**” denote significance levels of and , respectively, from a two-sided paired t-test when comparing our best model with others. The best results are shown in bold.